2021
DOI: 10.1002/lary.29554
|View full text |Cite
|
Sign up to set email alerts
|

Application of INSM1 in Diagnosis and Grading of Laryngeal Neuroendocrine Carcinoma

Abstract: Objective: Chromogranin (CHG), synaptophysin (Syn), and CD56 are generally used in a panel to support diagnoses of laryngeal neuroendocrine carcinomas (NECs). However, the absence of expression of these markers does not completely exclude the diagnosis. INSM1 is a novel marker that is considered sufficiently sensitive and specific for NE differentiation. The aim of this study is not only to detect its sensitivity and specificity, but also to evaluate its application in grading for laryngeal NECs.Methods: The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[8] Yuan et al performed immunohistochemical staining of INSM1, CgA, Syn, and CD56 in pathological samples of 25 laryngeal NENs and the results showed that INSM1 had a higher sensitivity (92%) and specificity (91%) compared to the other 3. [16] Ki-67 as a proliferative marker, combined with mitotic counting and necrosis, can be used to grade laryngeal NENs. The applications of calcitonin, CEA, and TTF1 in head and neck tumors have primarily focused on thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Yuan et al performed immunohistochemical staining of INSM1, CgA, Syn, and CD56 in pathological samples of 25 laryngeal NENs and the results showed that INSM1 had a higher sensitivity (92%) and specificity (91%) compared to the other 3. [16] Ki-67 as a proliferative marker, combined with mitotic counting and necrosis, can be used to grade laryngeal NENs. The applications of calcitonin, CEA, and TTF1 in head and neck tumors have primarily focused on thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…INSM1 is a transcription factor that induces differentiation in neuroendocrine cells or tumor cells in various organs, and many reports have shown its usefulness in diagnosis and treatment, including molecular-targeted therapy. In various tumors, such as thoracic tumors, laryngeal neuroendocrine carcinomas, and pancreatic neuroendocrine tumors, differences in sensitivity, specificity, and staining have been reported compared with classical markers, such as synaptophysin, chromogranin, and CD56 [ 5 , 14 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Ki-67 is deemed to be the most frequently used biomarker of prognosis, which is the basis for grading of NET. 2 In addition, Yuan et al 11 have suggested that INSM1 is of great significance in the diagnosis and classification of NEC of the larynx.…”
Section: Discussionmentioning
confidence: 99%